Compulsive‐like eating of high‐fat high‐sugar food is associated with 'addiction‐like' glutamatergic dysfunction in obesity prone rats. (13th July 2022) - Sketriene, Diana; Battista, Damien; Lalert, Laddawan; Kraiwattanapirom, Natcharee; Thai, Han Ngoc; Leeboonngam, Tanawan; Knackstedt, Lori A.; Nithianantharajah, Jess; Sumithran, Priya; Lawrence, Andrew J.; Brown, Robyn M.
Abstract: Chronic overeating is a core feature of diet‐induced obesity. There is increasing evidence that in vulnerable individuals, such overeating could become compulsive, resembling an addictive disorder. The transition to compulsive substance use has been linked with changes at glutamatergic synapses in the nucleus accumbens. In this study, we investigated a potential link between such glutamatergic dysregulation and compulsive‐like eating using a rat model of diet‐induced obesity. A conditioned suppression task demonstrated that diet‐induced obese rats display eating despite negative consequences, as their consumption was insensitive to an aversive cue. Moreover, nucleus accumbens expression of GluA1 and xCT proteins was upregulated in diet‐induced obese animals. Lastly, both a computed 'addiction score' (based on performance across three criteria) and weight gain were positively correlated with changes in GluA1 and xCT expression in the nucleus accumbens. These data demonstrate that the propensity for diet‐induced obesity is associated with compulsive‐like eating of highly palatable food and is accompanied by 'addiction‐like' glutamatergic dysregulation in the nucleus accumbens, thus providing neurobiological evidence of addiction‐like pathology in this model of obesity. Abstract : Using the conditioned suppression of eating paradigm, we show that diet‐induced obese (DIO) rats fail to reduce their kcal intake and latency to start eating in the presence of an aversive signal (cue light that previously signalled foot shocks). Eating despite negative consequences in DIO rats was accompanied by an increase in the addiction score and dysregulated glutamate in the nucleus accumbens (NAc).